Brave new Arctic : the untold story of the melting North - Serreze, Mark C. (Science essentials (National Academy of Sciences (U.S.)), 2018)
In the 1990s, researchers in the Arctic noticed that floating summer sea ice had begun receding. This was accompanied by shifts in ocean circulation and unexpected changes in weather patterns throughout the world. The Arctic's perennially frozen ground, known as permafrost, was warming, and treeless tundra was being overtaken by shrubs. What was going on? Brave New Arctic is Mark Serreze's riveting firsthand account of how scientists from around the globe came together to find answers.